2019
DOI: 10.1186/s13011-019-0230-5
|View full text |Cite
|
Sign up to set email alerts
|

Gambling symptoms, behaviors, and cognitive distortions in Japanese university students

Abstract: BackgroundThis study was conducted to investigate the relationship between symptoms of gambling problems, gambling behaviours, and cognitive distortions among a university student population in Japan ages 20 to 29 years. We aimed to address the gap in knowledge of gambling disorders and treatment for this population.MethodsData were obtained from 1471 Japanese undergraduate students from 19 universities in Japan. Descriptive statistics and hierarchical multivariate regression analysis were used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Excessive gambling also causes substantial stigma for the individual gamblers and their significant others (debt, unemployment, crimes such as embezzlement, theft, fraud, etc.). Despite a number of studies with epidemiological or psychiatric perspectives on gambling (e.g., Akiyama et al, 2019;Horiuchi et al, 2018;Yokomitsu et al 2019), there is a lack of research from a social (Takiguchi & Rosenthal, 2011) and qualitative point of view giving Japanese gamblers a voice.…”
Section: Shame Guilt and Stigma Of Gambling Problemsmentioning
confidence: 99%
“…Excessive gambling also causes substantial stigma for the individual gamblers and their significant others (debt, unemployment, crimes such as embezzlement, theft, fraud, etc.). Despite a number of studies with epidemiological or psychiatric perspectives on gambling (e.g., Akiyama et al, 2019;Horiuchi et al, 2018;Yokomitsu et al 2019), there is a lack of research from a social (Takiguchi & Rosenthal, 2011) and qualitative point of view giving Japanese gamblers a voice.…”
Section: Shame Guilt and Stigma Of Gambling Problemsmentioning
confidence: 99%
“…The facilitation of access to gambling‐based games, advertisements promoting gambling, the presence of gambling‐based games that are operated by various public institutions and integrated into the culture, the peer effect, and the presence of gambling in family members can be the reasons of gambling behaviors among young individuals (Nowak & Aloe, 2014). A large majority of the youth have played different types of gambling‐based games through the national lottery, scratch‐and‐win cards, and electronic gambling machines (Yokomitsu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a nationwide prevalence study revealed that approximately 1.5% of participants were classified as probably being affected by a gambling disorder [3]. Moreover, 5.1% of probable gambling disorders have been reported among college and university students in Japan [4]. One of the essential characteristics of gambling in Japan is the type of gambling accessible to gamblers.…”
Section: Introductionmentioning
confidence: 99%
“…One of the essential characteristics of gambling in Japan is the type of gambling accessible to gamblers. In Yokomitsu et al's [4] study, pachinko and slot machines (called pachislot in Japan) were the most common types of gambling activities that university students had engaged in. In addition, Shoun et al conducted a questionnaire study on 5,060 Japanese adults aged from 18-79 years through a low-coverage error sampling method and found that 11.5% of them (n= 582) had played pachinko or pachislot in the past 12 months [5].…”
Section: Introductionmentioning
confidence: 99%